Świat i rzeczywistość. O radości jako współ-istnieniu - Tadeusz Sławek (Fabrica Litterarum Polono-Italica, 2024)
Starting from Coleridge’s ode On Dejection the essay attempts to define complex relationships between dejection and joy also in the domain of pedagogy conceived of as the exercise in practicing the art of living. Faust’s complaint of the elimination of joy from teaching and learning clearly aims at a larger social project: a society of people who are active and critically assess social and political reality of the day. “Training”, which education has become, adapts the individual to perform repetitive tasks in order to adapt well to an increasingly mechanistic world. Already in the early decades of the 19th century, Thomas Carlyle said that if he had been looking for a single term to describe the new age, he would have found it in the word 'mechanical'. We understand joy as an inclusive rationality that not only allows for that which does not submit to the rigours of the currently valid understanding of rationality, but is capable of taking a step back on the path of “progress” made under the sign of rationality. It turns out to be necessary to accept the postulate of multiple ways of domiciling in the world, all of which apply in a “mild way”. Such mildness creates the right aura for the joy that comes from the practice of co-being with others.